The Influence of Destination Image and Islamic Value On Perceived Value and Satisfactin (Survey On Moslem Tourist of Halal Tourism In Banyuwangi) - Siti Zulaikhah; Any Urwatul Wusko; Andriani Kusumawati (Brawijaya University, 2023)
In Indonesia, halal tourism started to develop, this is happening because of the increasing number of tourists who are interested in halal tourism. Researchers want to contribute to the field of marketing management, especially those related to halal tourism. Samples from this study were 189 visitors, an accidental sampling technique. The results showed that: Destination Image has a significant effect on Perceived Value, Islamic Value has a significant effect on Perceived Value, Destination Image has no significant effect on Satisfaction, Islamic Value has a significant effect on Satisfaction, Perceived Value has a significant effect on Satisfaction, 2 results from the relationship that is not hypothesized, namely and Destination Image has a significant effect on Satisfaction through Perceived Value, Islamic Value has a significant effect on Satisfaction through Perceived Value.